MODELING AND SIMULATION OF THE BIOSURFACTANT PRODUCTION BY ENZYMATIC ROUTE USING XYLOSE AND OLEIC ACID AS REAGENTS: Scientific paper - Moulin Cansian, Ana Bárbara; Waldir Tardioli, Paulo; Furlan, Felipe Fernando; de Sousa Júnior, Ruy (Chemical Industry & Chemical Engineering Quarterly, 2022)
The biosynthesis of sugar esters, molecules with biosurfactant properties, can occur through the esterification of sugars with fatty acids by enzymatic catalysis. An alternative to reduce the impact of raw materials on the final biosurfactant production cost and the reuse of industrial waste is to use residues from vegetable oil industries as a source of free fatty acids, such as oleic acid, and lignocellulosic residues of 2G ethanol as a source of sugar (xylose). In this scenario, the present work aimed at modeling the biosurfactants production via heterogeneous biocatalysis using lipase, oleic acid, and xylose. Product separation and purification were performed using a sequence of precipitations (adding ethanol, water, and methyl ethyl ketone). The simulation was performed using the equation-oriented software EMSO (Environment for Modeling, Simulation, and Optimization), CAPE-OPEN compliant. The percentage of biosurfactants in the product was around 86%, with a recovery of 88% in the purification. Regarding the study of energy expenditure, a value of -604.1 kW of heat associated with cooling and a value of 137.6 kW associated with heating was observed. Developed mathematical models successfully described the process. The initial economic analysis of the process indicates a minimum biosurfactant selling price of US$ 72.37/kg.